A pedometer-based walking intervention with and without email counseling in general practice: a pilot randomized controlled trial - Tomas Vetrovsky; Jozef Cupka; Martin Dudek; Blanka Kuthanova; Klaudia Vetrovska; Vaclav Capek; Vaclav Bunc (BMC, 2018)
Abstract Background General practitioners play a fundamental role in combatting the current epidemic of physical inactivity, and pedometer-based walking interventions are able to increase physical activity levels of their patients. Supplementing these interventions with email counseling driven by feedback from the pedometer has the potential to further improve their effectiveness but it has to be yet confirmed in clinical trials. Therefore, the aim of our pilot randomized controlled trial is to evaluate the feasibility and potential efficacy of future trials designed to assess the additional benefit of email counseling added to a pedometer-based intervention in a primary care setting. Methods Physically inactive patients were opportunistically recruited from four general practices and randomized to a 12-week pedometer-based intervention with or without email counseling. To explore the feasibility of future trials, we assessed the speed and efficiency of recruitment, adherence to wearing the pedometer, and engagement with email counseling. To evaluate the potential efficacy, daily step-count was the primary outcome and blood pressure, waist and hip circumference, and body mass were the secondary outcomes. Additionally, we conducted a qualitative analysis of structured interviews with the participating general practitioners. Results The opportunistic recruitment has been shown to be feasible and acceptable, but relatively slow and inefficient; moreover, general practitioners selectively recruited overweight and obese patients. Patients manifested high adherence, wearing the pedometer on 83% (± 20) of days. All patients from the counseling group actively participated in email communication and responded to 46% (± 22) of the emails they received. Both groups significantly increased their daily step-count (pedometer-plus-email, + 2119, p = 0.002; pedometer-alone, + 1336, p = 0.03), but the difference between groups was not significant (p = 0.18). When analyzing both groups combined, there was a significant decrease in body mass (− 0.68 kg, p = 0.04), waist circumference (− 1.73 cm, p = 0.03), and systolic blood pressure (− 3.48 mmHg, p = 0.045). Conclusions This study demonstrates that adding email counseling to a pedometer-based intervention in a primary care setting is feasible and might have the potential to increase the efficacy of such an intervention in increasing physical activity levels. Trial registration The trial was retrospectively registered at ClinicalTrials.gov (ID: NCT03135561, date: April 26, 2017).